Numerical Analysis of Rock-Socketed Piles under Combined Vertical-Lateral Loading. (2017) - Singh, A.P.; Bhandari, T.; Ayothiraman, R.; Rao, K. Seshagiri
Abstract: This paper presents the results of numerical analysis carried out using PLAXIS 3D on behaviour of rock-socketed pile subjected to independent and combined loading. The numerical procedure adopted in the analysis was validated by comparing the load test results reported in the literature. After validation of the numerical analyses, the parametric analysis were performed on the rock-socketed pile subjected to independent loading and combined loading for different rock conditions, soil cover depths and socketing lengths. From the results of parametric study, it is found that the vertical and lateral load capacities under combined loading are not significantly affected, when the soil cover depth is high. However, if the soil cover depth is low, then the behaviour of rock-socketed pile under combined loading is found to be significantly different, compared to its behaviour under independent loading. It is also seen that the rock conditions and socketing length have profound effect on pile behaviour under combined loading.